University Students' Readiness for Using Digital Media and Online Learning-Comparison between Germany and the USA - Julian Küsel; Florence Martin; Silvija Markic (MDPI AG, 2020)
The year 2020 brought many changes to our everyday life but also our education system. Universities needed to change their teaching practices due to the COVID-19 pandemic. Words like "digital media", "online teaching" and "online learning" were present in all of the discussions. The main issues here were the technical infrastructure of students and universities all over the world. However, to have good technical infrastructure does not mean that everybody is also ready to use it. Thus, the present study focused on the issue of university students' readiness for online learning. The quantitative research goal was to evaluate German university students' readiness for using digital media and online learning in their tertiary education and compare them with students from the United States. Overall, 72 students from the researchers' university in Germany and 176 students from multiple universities in the United States completed the Student Readiness of Online Learning (SROL) questionnaire. Results show substantial differences between the two groups of students, with U.S. students being more ready for online learning. The results and limitations were discussed, and practical implications and further ideas were provided.